A Study of Understand the Weighted Maxwell- Boltzmann Distribution: Exploring the Statistical Distribution of Particle Speed in an Idealized Gas (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The Maxwell Distribution is often used in physics, especially statistical mechanics, to describethe speed of a particle in an idealized gas. James Clerk Maxwell, a Scottish physicist, suggested thisdistribution in 1859. In 1871, a German scientist named Ludwig Boltzmann built on Maxwell's work toexplain how energy is distributed among molecules. The speed of a particle travelling through threedimensionalspace may be seen as a collection of independent and normally distributed random variables,each with a mean and variance equal to one-third of the rate parameter, which is the focus of the majorityof the study.Derivation of weighted Maxwell-Boltzmann distribution, weighted distribution, Maximumlikelihood estimation, Structural properties, Estimation of parameters, Maximum likelihood estimation